Developing The Super Sehat Program: A Model for Promoting Healthy Living and Balanced Nutrition in Early Childhood Education - Ni Kadek Damiati; Gede Wira Bayu; Ni Ketut Desia Tristiantari (Universitas Pendidikan Mandalika, 2026)
This study aims to develop the SUPER SEHAT Program to improve clean and healthy living behaviors and understanding of balanced nutrition among early childhood children at Pelangi School Bali. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants included 42 early childhood children aged 4–6 years and two classroom teachers. Data were collected using observation sheets, expert validation instruments, and teacher response questionnaires. The instruments were used to measure children’s clean and healthy living behaviors, balanced nutrition understanding, program validity, and practicality. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that the SUPER SEHAT Program achieved a high validity score from experts, with a mean score of 3.79 out of 4.00, and was considered highly practical based on teacher responses, with a mean score of 3.81 out of 4.00. The effectiveness test revealed significant improvements in children’s clean and healthy living behaviors (Z = -5.656, p < .001) and balanced nutrition understanding (Z = -5.671, p < .001) after the implementation of the program. These findings indicate that the SUPER SEHAT Program is a valid, practical, and effective health education program for early childhood settings. Therefore, the program can serve as an alternative model for promoting healthy habits and supporting health-oriented learning in early childhood education.